The Church as Res Publica - Cyril Hovorun (Religions)
Christianity emerged valuing horizontal socio-political relations, which it inherited from Jesus Christ, and which resonated with the ideals of ancient Greek and Roman republicanism. As the church engaged with the Roman Empire, its republican roots faded, adopting monarchical traits. Still, republicanism never disappeared from the church or the Christian Empire. In the former, it took the form of synodality and became reflected in the ways of electing bishops. In the latter, the church became a part of the power-sharing system, effectively substituting the Senate. In contrast to the stereotype that the church is intrinsically monarchical and supports monarchies, this paper argues that the original Christian ethos is more republican than monarchical. As a result, the church has the potential to enhance democracies in the modern geopolitical landscape.